KONVERSI ASAM OLEAT MENJADI BIODIESEL MENGGUNAKAN KATALIS HETEROGEN CaO CANGKANG KEPITING TEREMBANKAN ?-Al2O3 - Handayani, Y. N.; Simpen, I N.; Negara, I. M. S. (Jurnal Kimia (Journal of Chemistry), 2022)
Heterogeneous catalysts are commonly used in biodiesel production. The CaO heterogeneous catalyst can be prepared by calcination process from one source of CaCO 3  prepared from crab shell. The preparation of heterogeneous catalyst was successfully carried out by activation with KOH and doped with ?-Al 2 O 3.  The purpose of this study is to determine the characteristics of the CaO/?-Al 2 O 3 heterogeneous catalyst and the performance of the catalyst for converting oleic acid into biodiesel. The results of this study that the best characteristics of catalyst were shown by CaO/?-Al 2 O 3  100:7, which has a surface basicity was 20,9532 mmol g -1  with active sites 12,6181x10 19 atom g -1 , and specific surface area of ??42.0979 m 2 /g. The results of using CaO /?-Al 2 O 3  catalyst for converting oleic acid into biodiesel with the optimum concentration was 5%, the optimum oil/methanol molar ratio of 1:9, and the optimum reaction time of 120 minutes for converting oleic acid into biodiesel with the yield of 89.80%. The characteristics of the final biodiesel obtained had met the Indonesian National Standard (SNI 7182-2015) with density (at 40 o C), kinematic viscosity (at 40 o C), water content, iodine value were 863 kg/m 3 ; 4.8 cSt; 0.039%, and 35.3562 g I 2 /100g, respectively. Keywords : CaO/?-Al 2 O 3 , oleic acid,biodiesel, heterogeneous catalyst.